PERAN STRUKTUR CORPORATE GOVERNANCE DALAM TINGKAT KEPATUHAN MANDATORY DISCLOSURE IFRS - Sean Archie Ago Tondombala; Hexana Sri Lastanti (Jurnal Akuntansi Trisakti, 2016)
The objective of this study is to find out the effect of corporate governance structure which is proxied by managerial ownership, institutional ownership, the number of board of commissioner meetings, the number of audit committee meetings, the proportion of independent commissioner and the amount of audit committee to the level of compliance with IFRS mandatory disclosure. The independent variables in this study are managerial ownership, institutional ownership, the number of board of commissioner meetings, the number of audit committee meetings, the proportion of independent commissioners and the amount of audit committee. The dependent variable in this study is the level of compliance with IFRS mandatory disclosure. Samples that used in this study were coal mining company listed on the Indonesia Stock Exchange (IDX) 2011-2013, there are 18 companies choosed with a sampling technique using purposive sampling method. This study uses multiple regression statistical technique (multiple regression model) to test the effect of independent variables on the dependent. The program used for hypothesis testing is SPSS 22. The results of this research indicates that the independent variables which managerial ownership, institutional ownership and the proportion of independent commisioners affect the level of compliance with IFRS mandatory disclosure. While theother independent variables are the number of board of commissioner meetings, the number of audit committee meetings and the amount of audit committee has no effect on the level of compliance with IFRS mandatory disclosure.